Undifferentiated necrotizing ulcerative vasculitis in a patient with pneumonia and stage 5 chronic kidney disease-a case report - Karpovich, Yulia; Sadadiwala, Mehul Hitesh; Mevawala, Hardik Bakulkumar; Ribadiya, Fenilkumar Nitinbhai; Bogdanovich, Vladimir (International Journal of Research in Medical Sciences, 2023)
Skin is a frequently involved and damaged organ in cutaneous necrotizing vasculitis (CNV), mainly characterized histologically by a segmental angiocentric inflammatory condition with fibrinoid necrosis of the vessel wall. Various etiological factors have been described as probable causes that trigger CNV, ranging from infectious causes to autoimmune conditions. We have described a case of a middle-aged man with chronic kidney disease (CKD) that presented to the Grodno university clinic with Staphylococcal pneumonia and high level of the IgE antibodies that probably triggered CNV. Written consent was taken from the patient mentioned in the study. The study was approved by the hospital and institutional ethics committee. Based on the provisional diagnosis of hemorrhagic necrotizing vasculitis (cutaneous form), the patient was started on a low dose of glucocorticosteroid therapy. After carrying out a skin flap biopsy, a confirmed diagnosis of ANCA-negative CNV-leukocytoclastic vasculitis (LcV) form was made. The patient was started on steroid pulse therapy followed by plasmapheresis for elevated IgE count, leading to rapid resolution of symptoms. Literature has stated that CNV-LcV form commonly involves immune complexes composed of IgG or IgM. Based on our observation, we have proposed a novel hypothesis that elevated IgE and IgE immune complexes can be an additional triggering factor for CNV-LcV form as well.